2016
DOI: 10.1080/21548455.2016.1200155
|View full text |Cite
|
Sign up to set email alerts
|

Learning with dinosaurs: a study on motivation, cognitive reasoning, and making observations

Abstract: Dinosaurs have been a very popular science topic since signs of their presence on earth were first discovered. They have represented so-called 'edutainment' for some people. Learning from informal sources and inan out-of-school environment can be effective and motivating. In this study, 12-year-old pupils (N = 366) visited a dinosaur science centre exhibition in Finland. Pupils were tested with standardised tests of motivation as defined by self-determination theory, cognitive skills, and interest via pre-, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 49 publications
0
7
1
Order By: Relevance
“…This is in line with some recent results relating to a dinosaur exhibition and the use of AR (Augmented Reality) in informal learning [61]. However, these results contradict the earlier reports in the literature [cf.…”
Section: Discussioncontrasting
confidence: 57%
“…This is in line with some recent results relating to a dinosaur exhibition and the use of AR (Augmented Reality) in informal learning [61]. However, these results contradict the earlier reports in the literature [cf.…”
Section: Discussioncontrasting
confidence: 57%
“…Lückmann and Menzel (2014) found that teenagers knew trees better than herbs, suggesting a stronger interest in larger woody plants. Further, a link to large creatures of the deep past has frequently been pointed out as a factor that can create fascination and hold attention (Chang, 2000;Vujakovic, 2016Vujakovic, [2013Salmi et al, 2017). The paleoecogical dimension in this work was clearly new to most students, who also appeared not to be used to linking information from other dimensions of knowledge to "school" or "college" biology.…”
Section: Tracking the Elusive Creaturementioning
confidence: 86%
“…Slayter and Higgins (2018) combined problem-oriented and hands-on learning to cultivate Microsoft Excel expertise. Research indicates hands-on learning eases learning difficulties (Brigham et al, 2011; Salmi et al, 2017) and augments learning effectiveness (Ballantyne & Packer, 2009).…”
Section: Related Workmentioning
confidence: 99%